8-Oxoguanine accumulation in aged female brain impairs neurogenesis in the dentate gyrus and major island of Calleja, causing sexually dimorphic phenotypes. (September 2019) - Haruyama, Naoki; Sakumi, Kunihiko; Katogi, Atsuhisa; Tsuchimoto, Daisuke; De Luca, Gabriele; Bignami, Margherita; Nakabeppu, Yusaku
Highlights: MTH1 and OGG1 prevent 8-oxoguanine accumulation in female brain during aging. 8-Oxoguanine accumulates in nuclear DNA of neural progenitors in female mice. 8-Oxoguanine accumulated in female neural progenitors is derived from 8-oxo-dGTP. 8-Oxoguanine accumulation impairs neurogenesis, locomotor and cognitive functions. Abstract: In mammals, including humans, MTH1 with 8-oxo-dGTPase and OGG1 with 8-oxoguanine DNA glycosylase minimize 8-oxoguanine accumulation in genomic DNA. We investigated age-related alterations in behavior, 8-oxoguanine levels, and neurogenesis in the brains of Mth1 / Ogg1 -double knockout (TO-DKO), Ogg1 -knockout, and human MTH1-transgenic (hMTH1-Tg) mice. Spontaneous locomotor activity was significantly decreased in wild-type mice with age, and females consistently exhibited higher locomotor activity than males. This decrease was significantly suppressed in female but not male TO-DKO mice and markedly enhanced in female hMTH1-Tg mice. Long-term memory retrieval was impaired in middle-aged female TO-DKO mice. 8-Oxoguanine accumulation significantly increased in nuclear DNA, particularly in the dentate gyrus (DG), subventricular zone (SVZ) and major island of Calleja (ICjM) in middle-aged female TO-DKO mice. In middle-aged female TO-DKO mice, neurogenesis was severely impaired in SVZ and DG, accompanied by ICjM and DG atrophy. Conversely, expression of hMTH1 efficiently suppressed 8-oxoguanine accumulation in both SVZ and DG with hypertrophy of ICjM. These findings indicate that newborn neurons from SVZ maintain ICjM in the adult brain, and increased accumulation of 8-oxoguanine in nuclear DNA of neural progenitors in females is caused by 8-oxo-dGTP incorporation during proliferation, causing depletion of neural progenitors, altered behavior, and cognitive function changes with age.